Recombinant Pseudomonas Vaccine: Technological Aspects of Obtaining and Evaluating Quality Indicators - Mihailova, Natalia A.; Kaloshin, Alexei A.; Zimina, Ekaterina M.; Soldatenkova, Alena V.; Kalinichenko, Evgeniy O.; Borisova, Olga V. (KnE Life Sciences, 2022)
For an aim to prevent Pseudomonas aeruginosa, a candidate recombinant vaccine has been developed. This vaccine – (RPV) was based on two protective proteins of P. aeruginosa: the outer membrane protein F (OprF) and the recombinant truncated form of the Exotoxin A (toxoid) that were adsorbed on the aluminum hydroxide. The optimal immunization schedule for mice included two intraperitoneal administrations with a two-week interval. RPV promoted to increase survival rates in challenged immunized mice and stimulated humoral and innate immune responses. During preclinical studies, we confirmed the immunogenicity of the vaccine that had not pyrogenicity, acute and chronic toxicity, allergenicity and immunotoxicity. Keywords: Pseudomonas aeruginosa, outer membrane protein F (OprF), toxoid, Pseudomonas Recombinant Vaccine (PRV)